2015
DOI: 10.1097/bpo.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Closed Reduction and Percutaneous Pinning of Displaced Pediatric Lateral Condyle Fractures of the Humerus

Abstract: CRPP is a viable alternative for the treatment of pediatric LCFs with limited initial displacement (between 2 and 4 mm). In addition to the obvious cosmetic advantage of avoiding an unsightly scar, it is associated with decreased surgical times and does not significantly increase the incidence of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 5 publications
(14 reference statements)
0
66
0
1
Order By: Relevance
“…Now this CRPP technique has been introduced in the latest edition of a classic book, Rockwood and Wilkins Fractures in Children [1]. A few later studies reported their results using this technique [15][16][17][18]. Silva et al claimed that CRPP is an alternative treatment of pediatric LCFs with displacement between 2 and 4 mm.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Now this CRPP technique has been introduced in the latest edition of a classic book, Rockwood and Wilkins Fractures in Children [1]. A few later studies reported their results using this technique [15][16][17][18]. Silva et al claimed that CRPP is an alternative treatment of pediatric LCFs with displacement between 2 and 4 mm.…”
Section: Discussionmentioning
confidence: 99%
“…CRPP has shown several advantages over ORIF, including less dissection of soft tissue around the fragment, low risk of vessel damage, low risk of non-union and AVN of distal humerus physes, shorter operating room times, and avoidance of an open incision with unaesthetic scar [15,19], avoidance of another operation or anesthesia because of hardware removal. The present study demonstrated that closed reduction and percutaneous pinning is a novel and feasible technique for treating LCHFs with displacement more than 4 mm, and more than 3/4 of Song stage V or Jakob type III patients can avoid an incision.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations